Strategic alliance in civil aviation industry: A case study of China Southern Airlines withdraw Sky Team Alliance - Haoxuan Luo (2019)
The fast development and expansion of airlines alliance since 1970s bring great convenience to people's traveling and create great value for the whole transportation industry. With the practice of Standardized service process, code-sharing and other resource sharing, the civil aviation industry gradually formed the three major alliances "dominant" the world market pattern. While in order to reposition its development strategy and pursue new partnerships, member of Sky Team Alliance, China Southern Airlines announced to withdraw ST and turns to bilateral cooperation at capital level like joint venture and equity merger. This event is regarded as the start of revolution in civil aviation industry. This master thesis is presented as a form of case study, aimed to teach students to understand the implication and development of Strategic Alliance, cultivate the analyzing ability in order to apply theoretical knowledge in realistic situation. In order to achieve the aim, the lesson should be given in an animating way to attract students’ full attention so that participating class discussion actively can make sense. Hence, China Southern as the biggest airlines in Asian and Pacific area, whose strategy change has a significant impact on the industry pattern. In addition the diversities of its partnership strategy is research valuable. Based on this, students can not only obtain plenty of information to answer the questions, but also learn the diversity of strategic alliance from different aspects. In this case, qualitative method is the approach that deals with the resolution of issues generally. Under the approach, students will be divided into groups and make a discussion about the questions.